Fuzzy Logic of Work Conformity in Small Enterprises of Traditional Medicines - Eliza Dwinta; Ajie Kusuma; Baniady Gennody Pronosokodewa; Raden Jaka Sarwadhamana (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Good Manufacturing Practices for Traditional Medicine (CPOTB) certification given by National Food and Drug Agency (BPOM) to Small Enterprises of Traditional Medicines (UKOT) is a claim from the production process of traditional medicines that is in accordance with CPOTB. However, not all human resources at UKOT understand and apply existing guidelines in the work practices of traditional medicine production. This study aims to assess the conformity of work by calculating the gap between knowledge of work practices in human resources in one UKOT Yogyakarta with fuzzy method. This assessment is a quantitative, cross-sectional study using a questionnaire that was adapted and modified from six categories of cause and effect. Respondents included in this study were all human resources in UKOT as many as 24 people (total sampling). The results obtained from the gap calculation of work conformity based on the six categories are machinery that have positive values (0,1146). Human resources who work at UKOT have a good understanding of the CPOTB and are already good at implementing work practices in accordance with the CPOTB in the machinery category. The findings that personnel pass through the production area, storage area and quality control area, as well as analysis methods that have not been validated periodically, can be used as an ingredient for improvement by implementing corrective-action-preventive-action on order to improve the quality of work in accordance with CPOTB and guarantee the quality of traditional medicine products from the UKOT Yogyakarta.